55 Case study of project to decolonize medicine: the [real] reason for overdiagnosiscase study of project to decolonize medicine: the [real] reason for overdiagnosis. (20th August 2018) - Mohammed, Imran
Abstract : Overdiagnosis and a lack of an affordable healthcare system is due to an over emphasis on drug and technological solutions, which contributes approximately 15%–18% to the health of people; 'Social' (diet, education, exercise) and environmental (polluted air, food and water) issues having the biggest impact on health and quality of life as defined by WHO. This pattern was echoed in a report by National Academy of Sciences 2016: 'why despite a higher expenditure than any other country have we achieved less health?' 'a major reason lies in the fact that the foci of our attention, our resources and incentives are too narrow our investments… are directed to narrow biomedical (focus).' This Project carried out by me with Latino community in a social and economically deprived part of London, using indigenous food and values of community to improve health as well as reduce obesity. This has the potential to be a sustainable community led initiative that recognises the heritage and expertise that exists within these communities. This runs counter to the top down approach that leads to low value care Why have drug and technological interventions been privileged over social and environmental solutions? Since roughly late 1800s in (in the west) Disease was seen as a 'thing' in its own right, with a recognisable mechanism and predictable clinical course. This 'disease' carrying out its rampage on the patient regardless of his/her original health status or environment they live in. Medical technology (which we know can be so misleading and problematic) grew up around this to reinforce the identity and status of 'being' of the disease. This enabled a reinforcing of power structures normally ['white'] men and medical/political/economical hierarchies, to battle the terrible 'beings' from the 'barbaric ' and 'dirty east'. This led to disregard of the individual health status or environment the person lived in, hence a neglect at looking at solutions such as peoples original nutritional status, housing conditions or access to adequate sanitation. Primary Care as conceived in 1978 at the time of the WHO Alma Alta was a declaration of Philosophy of health to meet the community's needs (not business or political). Primary health Care was meant to be designed and built with community participation This project shows health problems as complex ecological systems, where context matters, with multiple solutions that can change in emphasis based on time and place.